Mechanisms Associated to Nitroxyl (HNO)-Induced Relaxation in the Intestinal Smooth Muscle - Gastreich-Seelig, Mirko; Jimenez, Marcel; Pouokam, Ervice (Frontiers in Physiology, 2020)
The role of nitroxyl (HNO) as signaling molecule in the gastrointestinal tract is not known. We investigated the properties of this signaling molecule in the regulation of gastrointestinal contractility focusing on its possible interaction with other gaseous signaling molecules such as NO and H2S. Organ bath, Ca2+ imaging and microelectrode recordings were performed on rat intestinal samples, using Angeli’s salt as HNO donor. Angeli’s salt caused a concentration-dependent relaxation of longitudinal or circular muscle strips of the ileum and the proximal colon. This relaxation was strongly inhibited by the Rho-kinase inhibitor Y-27632 (10 µM), by the reducing agent DTT or by the inhibitor of soluble guanylate cyclase (sGC) ODQ (10 µM) alone or in combination with the inhibitors of the endogenous synthesis of H2S β-cyano-L-alanine (5 mM) and amino-oxyacetate (5 mM). Preventing endogenous synthesis of NO by the NO synthase inhibitor L-NAME (200 µM) did not affect the relaxation induced by HNO. HNO induced an increase of cytosolic Ca2+ concentration in colonic myocytes. It also elicited myocyte membrane hyperpolarization that amounted to -10.6 ± 1.1 mV. ODQ (10 µM) and Apamin (1 µM), a selective inhibitor of small conductance Ca2+-activated K+ channels (SK), strongly antagonized this effect. We conclude that HNO relaxes the gastrointestinal tract musculature by hyperpolarizing myocytes via activation of the sGC/cGMP pathway similarly to NO, inhibiting the RhoK and activating MLCP as do both NO and H2S, but also increasing cytosolic Ca2+ for activation of SKCa contributing to hyperpolarization.